Evaluation of Microwave Radiometer Sea Ice Concentration Products over the Baltic Sea - Marko Mäkynen; Stefan Kern; Rasmus Tonboe (Remote Sensing)
Sea ice concentration (SIC) monitoring in the Arctic using microwave radiometer data is a well-established method with numerous published accuracy studies. For the Baltic Sea, accuracy studies have not yet been conducted. In this study, we evaluated five different SIC products over the Baltic Sea using MODIS (250 m) and Sentinel-2 (10 m) open water–sea ice classification charts. The selected SIC products represented different SIC algorithm types, e.g., climate data records and near-real-time products. The one-to-one linear agreement between the radiometer SIC dataset and the MODIS/Sentinel-2 SIC was always quite poor; the slope of the linear regression was from 0.40 to 0.77 and the coefficient of determination was from 0.26 to 0.80. The standard deviation of the difference was large and varied from 15.5% to 26.8%. A common feature was the typical underestimation of the MODIS/Sentinel-2 SIC at large SIC values (SIC > 60%) and overestimation at small SIC values (SIC < 40%). None of the SIC products performed well over the Baltic Sea ice, and they should be used with care in Baltic Sea ice monitoring and studies.